Jade war - Lee, Fonda (The Green Bone saga, 2019)
"In Jade War, the sequel to the Nebula, Locus, and World Fantasy Award-nominated Jade City, the Kaul siblings battle rival clans for honor and control over an Asia-inspired fantasy metropolis. On the island of Kekon, the Kaul family is locked in a violent feud for control of the capital city and the supply of magical jade that endows trained Green Bone warriors with supernatural powers they alone have possessed for hundreds of years. Beyond Kekon's borders, war is brewing. Powerful foreign governments and mercenary criminal kingpins alike turn their eyes on the island nation. Jade, Kekon's most prized resource, could make them rich - or give them the edge they'd need to topple their rivals. Faced with threats on all sides, the Kaul family is forced to form new and dangerous alliances, confront enemies in the darkest streets and the tallest office towers, and put honor aside in order to do whatever it takes to ensure their own survival - and that of all the Green Bones of Kekon"--